2019
DOI: 10.3390/jcm8030317
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Botulinum Toxin for Treating Sialorrhea in Patients with Parkinson’s Disease: A Systematic Review

Abstract: The main objective was to assess the efficacy of botulinum toxin-based treatment for sialorrhea in adult patients with Parkinson’s disease. The search was performed by using the Medline-PubMed, EMBASE and Cochrane Library databases from January 2000–December 2017, in English/Spanish in patients with Parkinson’s disease and sialorrhea. The methodological quality of trials was carried out by following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria and the Newcastle–Ottaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…In August 2019 rimabotulinumtoxinB was approved in the USA (1500-3000 units). More studies with larger samples and longer follow-up periods are desirable to confirm the recent data [106].…”
Section: Recommendationsmentioning
confidence: 75%
“…In August 2019 rimabotulinumtoxinB was approved in the USA (1500-3000 units). More studies with larger samples and longer follow-up periods are desirable to confirm the recent data [106].…”
Section: Recommendationsmentioning
confidence: 75%
“…Botulinum toxin therapy represents one of the many pharmacological strategies to reduce salivary flow, which is a major culprit in PCF formation and persistence [6 bomeli]. This molecule has been extensively used in the treatment of sialorrhea for many neurological syndromes [ 42 , 43 , 44 , 45 ]. Botulinum toxin starts to reduce the salivary secretion from 72 h after the periparotid infiltration and it has a more noticeable effect after 5 to 7 days [ 46 ]; its action is reversible and it lasts about 2–4 months, and with minimal systemic side effects [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have demonstrated that BoNT/A elicits neurotrophic effects via HC C /A-mediated activation of Rac1. Properly administered, BoNT/A has already been shown to be a safe drug and, indeed, it induces sprouting in nerves of patients suffering from Parkinson’s disease and amyotrophic lateral sclerosis ( Kulshreshtha et al, 2020 , Moller et al, 2011 , Ruiz-Roca et al, 2019 , Vazquez-Costa et al, 2016 ). Clearly, caution must be used when comparing the sprouting response at the neuromuscular junction in vivo with neurite outgrowth from cultured neurons.…”
Section: Discussionmentioning
confidence: 99%